KAJIAN TEORITIK PENGARUH GEOMETRI DAN SUDUT KEMIRINGAN TERHADAP KINERJA TURBIN ARCHIMEDES SCREW - Nugroho, Agung Dwi (SENATIK STT Adisutjipto, 2017)
The need for electrical energy is increasing every year. The present electrical energy remains largely dependent on fossil energy and can not be renewed. Indonesia is one of the countries rich in renewable energy potential. The abundant energy in Indonesia is water energy as a mini / microhydro scale generator. The development of hydro power is to utilize the potential energy flow of water that has certain head and debit. Then the potential energy is converted by turbine and generator into electrical energy. The purpose of this paper is to conduct a theoretical study to design the optimal angle of archimedes screw with a relatively easy design method. Based on the results obtained geometry and arch angle archimedes screw design with 0.050 m external diameter, 0.030 m internal diameter 0.055 m and slope  angle (α) 450 generates shaft power of 5.11 Watt at 50 rpm rotation capable of producing efficiency 89% with head 1 m and debit 0.5 m / s.